Estrategia pedagógica para desarrollar competencias investigativas (2011)
This work emerges from the need to find a solution to the research training issue at the Universidad de America undergraduate level after many attempts of strategies and, after the law to regulate universities operation was issued. A pedagogical model based on active and collaborative learning which methodological strategies promote the development of a conceptual, critical and scientific thinking, is proposed. As well, these strategies must develop skills and abilities that allow students to find solutions in the professional field. The model is structured on three areas of training: one focused on the development of skills to manage information, the second one in the development of thinking, and the third one on research competences.